2023
DOI: 10.3390/jpm13030513
|View full text |Cite
|
Sign up to set email alerts
|

An Angiogenesis-Related lncRNA Signature Is Associated with Prognosis and Tumor Immune Microenvironment in Breast Cancer

Abstract: Angiogenesis is crucial in the development and progression of tumors. This study examined the relationship between angiogenesis-related lncRNAs (AR-lncRNAs) and breast cancer (BC) immunity and prognosis. We used univariate Cox regression analysis to obtain AR-lncRNAs closely related to BC prognosis. Cluster analysis of BC patients was performed using non-negative matrix factorization (NMF) analysis according to the expression of AR-lncRNAs that were prognostically relevant. An AR-lncRNA risk model (AR-lncM) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
0
0
Order By: Relevance
“…While research on NDUFA6-DT in tumors and gliomas is currently limited, its increasing recognition in the field of oncology is extensive. Previous studies have identified NDUFA6-DT as a prognostic lncRNA in breast [31][32][33] and thyroid cancers [34]. Functioning as a protective factor, it carries potential implications as a cancer prognostic indicator and therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…While research on NDUFA6-DT in tumors and gliomas is currently limited, its increasing recognition in the field of oncology is extensive. Previous studies have identified NDUFA6-DT as a prognostic lncRNA in breast [31][32][33] and thyroid cancers [34]. Functioning as a protective factor, it carries potential implications as a cancer prognostic indicator and therapeutic target.…”
Section: Discussionmentioning
confidence: 99%
“…These biological activities supply plentiful oxygen and nutrients for rapid tumor growth. Advanced ccRCC is an angiogenesis-dependent tumor 10 , 11 . Therefore, angiogenesis-related biomarkers might be useful for assessing ccRCC prognosis.…”
Section: Introductionmentioning
confidence: 99%